Transient Leukoerythroblastic Reaction in a Newborn with Rh-Incompatibility and Hemolysis: Case Report and Literature Review - Arega G; Gashaw H; Muhammed Fedlu N; Ergete W (Dove Medical Press, 2023)
Gashaw Arega,1 Henock Gashaw,1 Nuru Muhammed Fedlu,1 Wondwossen Ergete2 1Department of Pediatrics and Child Health, School of Medicine, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Pathology, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Gashaw Arega, Department of Pediatrics and Child Health, School of Medicine, Addis Ababa University, P.O. Box 9080, Addis Ababa, Ethiopia, Email gashawarega@gmail.comAbstract: Leukoerythroblastosis is rarely encountered in clinical practice and is characterized by the presence of leukocytosis and erythroid and myeloid blast cells in peripheral blood. The most common causes of leukoerythroblastosis in early childhood are viral infection, juvenile myelomonocytic leukemia, and osteopetrosis. To the best of our knowledge, leukoerythroblastic reactions associated with hemolysis have not been previously reported in newborns. Here, we report a 24-hour-old female term newborn diagnosed with a leukoerythroblastic reaction, severe anemia, and neonatal hyperbilirubinemia secondary to Rh incompatibility based on presentation, laboratory determination, and peripheral morphology. A high index of clinical suspicion is required to avoid life-threatening complications among health professionals in the neonatal care unit.Keywords: newborn, Rh-incompatibility, hemolysis, leukoerythroblastic reaction